Robust comparison of climate models with observations using blended land air and ocean sea surface temperatures. Issue 15 (13th August 2015) - Cowtan, Kevin; Hausfather, Zeke; Hawkins, Ed; Jacobs, Peter; Mann, Michael E.; Miller, Sonya K.; Steinman, Byron A.; Stolpe, Martin B.; Way, Robert G.
Abstract The level of agreement between climate model simulations and observed surface temperature change is a topic of scientific and policy concern. While the Earth system continues to accumulate energy due to anthropogenic and other radiative forcings, estimates of recent surface temperature evolution fall at the lower end of climate model projections. Global mean temperatures from climate model simulations are typically calculated using surface air temperatures, while the corresponding observations are based on a blend of air and sea surface temperatures. This work quantifies a systematic bias in model‐observation comparisons arising from differential warming rates between sea surface temperatures and surface air temperatures over oceans. A further bias arises from the treatment of temperatures in regions where the sea ice boundary has changed. Applying the methodology of the HadCRUT4 record to climate model temperature fields accounts for 38% of the discrepancy in trend between models and observations over the period 1975–2014.